Color Image Steganography Based on Discrete Wavelet and Discrete Cosine Transforms - Abdul Latef, A. A. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The secure data transmission over internet is achieved using Steganography. It is the art and science of concealing information in unremarkable cover media so as not to arouse an observer’s suspicion. In this paper the color cover image is divided into equally four parts, for each part select one channel from each part( Red, or Green, or Blue), choosing one of these channel depending on the high color ratio in that part. The chosen part is decomposing into four parts {LL, HL, LH, HH} by using discrete wavelet transform. The hiding image is divided into four part n*n then apply DCT on each part. Finally the four DCT coefficient parts embedding in four high frequency sub-bands HH in cover image. Experiments show that this method gets stego image with perceptual invisibility, and better secrecy. The proposed method was implemented using MATLAB 7.8.